ANALISIS FAKTOR RESIKO SEPSIS NEONATORUM DI INDONESIA - Ferdian Syukri Arisqan (Jurnal Medika Hutama, 2021)
Sepsis is a major problem to date and is one of the top 10 causes of death in developing countries. Neonatal sepsis is a clinical syndrome caused by bacteria, viruses, and fungi characterized by systemic signs and symptoms and shows positive blood cultures occurring in the first month of life. The purpose of this literature review is to analyze the associated risk factors for neonatal sepsis, which are often found in Indonesia as a developing country. The method used is the literature review method from various national and international journals. From several studies conducted, it was found that the most common risk factors for neonatal sepsis in Indonesia as a developing country include premature rupture of membranes > 18 hours, preterm labor, low birth weight, babies born with low apgar scores, cloudy or smelly amniotic fluid. , and labor by caesarean section or using tools such as vacuum